2015
DOI: 10.1039/c5cp00552c
|View full text |Cite
|
Sign up to set email alerts
|

Influence of surface functionalization on the hydrophilic character of mesoporous silica nanoparticles

Abstract: We report the synthesis and surface functionalization of MCM-41-like mesoporous silica nanoparticles (MSNs) with spheroidal shape and particle size of 141 ± 41 nm. The success of surface functionalization with aminopropyl and sodium ethylcarboxylate groups (giving amino-MSN and carboxy-MSN, respectively) was ascertained by infrared spectroscopy and ζ potential measurements. The former showed the decrease of surface silanol groups and the corresponding appearance of signals related to NH2 bending mode (δNH2) at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 94 publications
3
53
1
Order By: Relevance
“…The negative charge increasing with pH (−35 mV at pH 11) is related to the deprotonation of Si–OH groups; similar results have been observed for silanol-rich mesoporous silica NPs. 28,29 On the other hand, for PEGylated Gd-LTL, the ζ values turn from positive to negative between pH 3 and 11 with an IEP at pH 5.6 and 8.3 for 6.2 and 9.1 wt % of PEG-loading, respectively. The changeover, becoming more pronounced with increasing PEG-grafting, is in good agreement with the results by He et al, who demonstrated that mesoporous silica NPs become less negatively charged upon increase of PEG-loading.…”
Section: Resultsmentioning
confidence: 99%
“…The negative charge increasing with pH (−35 mV at pH 11) is related to the deprotonation of Si–OH groups; similar results have been observed for silanol-rich mesoporous silica NPs. 28,29 On the other hand, for PEGylated Gd-LTL, the ζ values turn from positive to negative between pH 3 and 11 with an IEP at pH 5.6 and 8.3 for 6.2 and 9.1 wt % of PEG-loading, respectively. The changeover, becoming more pronounced with increasing PEG-grafting, is in good agreement with the results by He et al, who demonstrated that mesoporous silica NPs become less negatively charged upon increase of PEG-loading.…”
Section: Resultsmentioning
confidence: 99%
“…[19,[28][29][30][31][32][33][34] It can be obtained from organosilanes such as 3-aminopropyltriethoxysilane (APTS, the most commonly employed), 3-aminopropylmethyldiethoxysilane and 3-aminopropyl dimethylethox-ysilane. Moreover,s urfacef unctionalisationc an severelyi nfluencei mportant material properties such as surface charge, [32,34,42] hydrophilicity, [34,43,44] dispersibility, [22] toxicity [45] and stability. [42] This functionalisation is usually aimed at optimising the interaction with the desired target adsorptive: CO 2 in carbon capture and storagea pplications, pollutantsi ne nvironmental applications, reactants in catalysis, drugs in nanomedicine and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…The most utilized method is the measurement of the contact angle (θ , see also Figure ), that is, the optical measurement of the angle formed by substrate and the tangent at the droplet. An alternative method is for example the microgravimetric H 2 O adsorption–desorption isotherms to determine the hydrophobicity of microparticles …”
Section: Methodsmentioning
confidence: 99%
“…Monolayer absorption of molecules with specific characteristics also influences the surface behavior, as demonstrated by Musso et al. by modifying the hydrophobicity of mesoporous silica particles by grafting differently charged silane molecules on the surface …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation